Wasiat Wajibah Sebagai Jembatan Hukum Bagi Penyelesaian Masalah Kewarisan Perkawinan Beda Agama di Indonesia: Studi Terhadap Hukum Kewarisan Islam dan Hukum Kewarisan Perdata (BW) - Faradhilla Nursyahda; Windi Afdal; Winda Fitri (Universitas Muhammadiyah Ponorogo, 2026)
In the context of interfaith marriage, this study aims to investigate the differences in inheritance law regulations between Indonesian civil law and Islamic law. This study uses a normative juridical approach that combines conceptual, legislative, and comparative methodologies. The Civil Code, the Compilation of Islamic Law (KHI), and Supreme Court decisions are examples of primary legal materials; secondary legal elements are derived from literature and legal journals that are evaluated qualitatively. The findings show that, as long as it does not conflict with Article 838 of the Civil Code and allows for the use of wills, civil inheritance law does not view religious differences as an obstacle to inheritance. Islamic inheritance law, on the other hand, prohibits inheritance between people of different religions as stated in the KHI and hadith, but provides for a mandatory will as a substitute, with a maximum of one-third of the inheritance. To achieve legal certainty in Indonesia, this study finds that the wajibah will serves as a legal bridge to connect the principles of justice in Islamic law with the freedom to determine wills in civil law.